IMPACT OF ANTHROPOGENIC ACTIVITIES AND LAND USE ON WATER QUALITY: AN ANALYSIS IN MICROBASINS IN RIO GRANDE DO SUL, BRAZIL - Konzen, Isabela Schamann; Gamboa, Adriana; Gaida , William; Rosa, Genesio Mario da; Flach , Kauane Andressa; Bones, Ubiratan Alegransi; Breunig, Fabio Marcelo; Mendonça, Ângela Maria; Mahnke, Mathias Rezende; Maciel, Diego Hider (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2024)
In the dynamic interface of human activities and natural ecosystems, understanding the impact of anthropogenic interventions on water quality is of paramount importance. This research investigates the interplay between land use patterns and water quality in three microbasins of the Lajeado Três Passos River, located in Rio Grande do Sul, Brazil, which have intensive land use that can generate an impact on water quality. For this purpose, a land use and occupation study was conducted using Sentinel-2 imagery classification with a supervised method. Additionally, water samples were collected from the main channel and the three microbasins for the analysis of physicochemical and microbiological parameters following standardized methods, and the Trophic State Index was calculated. The results indicate a connection between urban coverage and elevated total solids, pH, nitrogen species, coliforms, and Escherichia coli content, along with hypereutrophic characteristics throughout the studied region. Our findings emphasize the importance of identifying and controlling pollution sources that may be affecting this aquatic system.